A conceptualization of corporate responsibility activity from the edge of Malaysia corporate / Mahadir Ladisma @ Awis, Hazman Shah Vijayan Abdullah and Norziana Lokman - Ladisma @ Awis, Mahadir; Vijayan Abdullah, Hazman Shah; Lokman, Norziana (Universiti Teknologi MARA, Shah Alam, 2016)
Corporate responsibility is one of the new corporate governance mantras that give some credence to stakeholder theory of corporations. Studies have examined the interest in the levels and effects of corporate social responsibility investments on employees, customers, and investors. Therefore, this paper aims to discuss on the history, definition and model of corporate responsibility which derived the various types of corporate responsibility activities. It is imperative among researchers to understand the various definitions and to explore the history of corporate responsibility. From the discussion and the arguments of scholars, this paper acknowledged and defined corporate responsibility as actions that appear to be the extension of some socially accepted manners within the interests of the firms which required by the law. Furthermore, corporate responsibility is beyond obeying the law, hence the need to design corporate responsibility activities as to reflect the stakeholder’s expectation.